2021
DOI: 10.1007/s00726-021-03012-9
|View full text |Cite|
|
Sign up to set email alerts
|

N-Propargylglycine: a unique suicide inhibitor of proline dehydrogenase with anticancer activity and brain-enhancing mitohormesis properties

Abstract: Proline dehydrogenase (PRODH) is a mitochondrial inner membrane flavoprotein critical for cancer cell survival under stress conditions and newly recognized as a potential target for cancer drug development. Reversible (competitive) and irreversible (suicide) inhibitors of PRODH have been shown in vivo to inhibit cancer cell growth with excellent host tolerance. Surprisingly, the PRODH suicide inhibitor N-propargylglycine (N-PPG) also induces rapid decay of PRODH with concordant upregulation of mitochondrial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…1A ). In agreement with our previous study in WT mice ( Scott et al, 2021 ), N -PPG also induced some evidence of mitohormesis in HD brain samples. Treated HD brains exhibited nominal (but insignificant) declines in Prodh protein levels associated with increases in Yme1l1 protease ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1A ). In agreement with our previous study in WT mice ( Scott et al, 2021 ), N -PPG also induced some evidence of mitohormesis in HD brain samples. Treated HD brains exhibited nominal (but insignificant) declines in Prodh protein levels associated with increases in Yme1l1 protease ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, until very recently no systemically well-tolerated, mitochondria-targeted, brain-penetrating, and mitohormesis-inducing drug candidate has been proposed and tested in vivo . In pursuing N -propargylglycine ( N -PPG) as a unique suicide inhibitor of mitochondrial proline dehydrogenase (Prodh) and potential anticancer therapeutic, we observed that, in both human cancer cells and normal mouse tissues, its irreversible inhibition and structural distortion of Prodh protein induces UPR mt and thereby activates mitohormesis, a property independent of N -PPG’s anticancer activity but consistent with its lack of any obvious host toxicity when administered orally for 9 days at 50 mg/kg ( Scott et al, 2019 ; Scott et al, 2021 ).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A number of agents have already been proposed and tested. Inhibitors and the enzymes they target include: tetrahydrofuroic acid, N -propargylglycine (Scott et al 2021 ) inhibitors of PRODH; NFLP, inhibitor of PYCR; halofuginone, inhibitor of prolyl t-RNA synthase; budesonide, inhibitor of collagen synthesis. These are published reports of inhibitors of the proline regulated axis and its downstream effectors (D'Aniello et al 2020 ).…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%